Pharmacology : PreTest Self-assessment and Review - DiPalma, Joseph R. (McGraw-Hill, 1988)
Designed to provide medical students with an instrument for self-assessment and review in the field of pharmacology. It contains 500 multiple-choice questions designed to parallel the questions contained in Step 1 of the United States Medical Licensure Examination